2017
DOI: 10.18203/issn.2455-4510.intjresorthop20175067
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of functional outcome following conservative versus surgical management in fractures of the distal radius

Abstract: <p class="abstract"><strong>Background:</strong> <span lang="EN-GB">Distal radial fractures are one of the most common injuries seen in the orthopaedic department, which can be managed both conservatively and surgically. There are advantages and disadvantages in each method of management. The aim of this study was to compare the functional and radiological outcomes of intra-articular fractures of the distal end of the radius with conservative and surgical management</span><span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…10 In a study by Subash Y, et al has shown in another study that frequency of excellent functional outcome was 30%, good 15%, fair 35% and poor was 20% after conservative treatment of distal radius fractures. 11 Koenig and colleagues conducted a comparative investigation assessing both conservative and surgical management approaches. Their study yielded the conclusion that open reduction and internal fixation with locking compression plates not only results in a higher rate of union but also leads to a superior functional outcome when contrasted with the use of casting in the treatment of these fractures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 In a study by Subash Y, et al has shown in another study that frequency of excellent functional outcome was 30%, good 15%, fair 35% and poor was 20% after conservative treatment of distal radius fractures. 11 Koenig and colleagues conducted a comparative investigation assessing both conservative and surgical management approaches. Their study yielded the conclusion that open reduction and internal fixation with locking compression plates not only results in a higher rate of union but also leads to a superior functional outcome when contrasted with the use of casting in the treatment of these fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size was calculated with WHO sample size calculator, using 95% confidence interval, 6% margin of error and expected prevalence of good functional outcome by 15% after conservative treatment of distal radius fractures. 11 Data was collected using Nonprobability consecutive sampling technique after ethical approval (Ref.78/OrthoB/HMC). Patient of both gender with age between 18 to 70 years with distal radius fracture of less than 48 hours duration was included in our study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation